GCT-03. MonoGerm: A proposed phase II trial of carboplatin or vinblastine monotherapy induction prior to radiotherapy for intracranial germinoma. (3rd June 2022) - Murray, Matthew; Apps, John; Lawson, Anna; Kirton, Laura; Peet, Andrew; Arvanitis, Theodoros; Fern, Lorna; Mitra, Dipayan; Coleman, Nicholas; Ajithkumar, Thankamma; Bison, Brigitte; Veal, Gareth; et al.
Abstract: BACKGROUND: Intracranial germinoma is chemosensitive but radiotherapy (RT) is needed for cure. In localised disease, three-drug standard-of-care (SOC) inpatient chemotherapy is used to reduce RT fields/dose. Concomitant diabetes insipidus is common, making chemotherapy delivery challenging. Small studies have demonstrated benefits from single-agent carboplatin or vinblastine in germinoma as an alternative to SOC. However, this needs prospective evaluation in a clinical trial. METHODS: We developed a trial, with a patient-public-involvement workstream, primarily evaluating whether single-agent chemotherapy (carboplatin or vinblastine) is non-inferior to SOC for inducing radiological complete response (CR) in localised disease, and is associated with reduced toxicity and improved quality-of-life (QoL), evaluated through patient-reported-outcome-measures (PROMs). RESULTS: The resultant proposed multi-centre, phase II proof-of-principle trial will investigate, in parallel, two single agents as monotherapy induction, in children/teenagers/adults with intracranial germinoma. Trial features include: a) Bayesian statistical design determining whether CR rate for either agent is sufficiently non-inferior to SOC; b) 'Flip-flop' design with alternating, continuous enrolment to the two single-agents, interim assessments after each recruited cohort, and early stopping rules for inferiority; c) Safety MRI, after 6-weeks of chemotherapy with real-time central-radiological-review; d) Proof-of-principle vinblastine monotherapy arm for metastatic patients awaiting definitive craniospinal-irradiation; e) State-of-the-art integrated imaging acquisition, QoL/PROM, pharmacokinetics and circulating microRNA studies to maximise information/learning; f) European and North American neuroradiological response criteria comparison and prospective evaluation of new consensus criteria. CONCLUSIONS: Trial results will: a) establish whether monotherapy is a treatment option in this setting, which may be practice-altering; b) use QoL/PROM data to inform on optimal treatment if results similar; c) use embedded radiological assessments to develop intracranial germinoma trials and facilitate European/US study comparisons; d) describe vinblastine pharmacokinetic data to inform future dosing schedules in this and other malignancies; and e) quantify circulating microRNAs, facilitating future non-invasive diagnosis/risk-stratification.